Bilateral Numb Chin Syndrome as the Initial Presentation of Burkitt’s Lymphoma/Leukemia: A Report of Two Cases and Review of the Literature - Algahtani, Hussein; Shirah, Bader; Bassuni, Wafaa; Adas, Reem (Case Reports in Hematology, 2016)
Numb chin syndrome, also known as mental nerve neuropathy, is a rare sensory neuropathy characterized by paresthesia and hypoesthesia in the area supplied by the mental nerve and its branches. This syndrome may be the first symptom of underlying malignancy or the first sign of recurrence and metastasis in patients with preexisting cancer. In this article, we present two cases with bilateral numb chin syndrome as the first manifestation of Burkitt’s lymphoma/leukemia and review the relevant literature. Numb chin syndrome should be considered as a warning sign and raise the suspicion for an underlying malignancy. Bilateral involvement is especially hazardous and must not be underestimated. In fact, an astute neurologist and internist who realizes that chin numbness is a potentially significant symptom can then exclude serious underlying malignancies. Standard diagnostic protocol with different modalities of imaging based on the availability and experience of the radiology team should be mandatory. High index of suspicion should be practiced to avoid delay in diagnosis and progression of the underlying malignancy.